The Use of Phase Measuring (Interferometric) Sonars: Choosing Appropriate Data Processing Methodologies - Hiller, Tom; Hogarth, Peter (The International Hydrographic Review, 2005)
Phase measuring bathymetric sonars (often mislabelled ‘interferometers’) are a popular tool for wide swath shallow water hydrography. Factors which affect the data quality from the newest generation of such systems are presented along with the data processing methodologies required to achieve high quality bathymetric maps meeting current survey standards. A brief look at a more formal statistical approach is taken in order to show that these processing methods (and the assumptions made) have a sound background. Data and charts from a widely used commercial system are included which illustrate the practical application of this theory.